2001
DOI: 10.1200/jco.2001.19.6.1734
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Two Years of Phase III Trials for Patients With Advanced Non–Small-Cell Lung Cancer: Sobering Results

Abstract: Analysis of past trials in North America shows that the prolongation in median survival between two arms of a randomized study was rarely in excess of 2 months. Techniques for improved use of patient resources and appropriate trial design for phase III randomized therapeutic trials with patients with advanced NSCLC need to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
174
1
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(184 citation statements)
references
References 35 publications
3
174
1
6
Order By: Relevance
“…Our results were consistent with those from a previous IPD-based analysis of ECOG trials, which reported improved survival in more recent NSCLC trials. 10 Breathnach et al, who investigated the changes in trial characteristics and outcomes of 33 Phase III trials that were initiated from 1973 to 1994 in North America, reported an improvement in survival over time (P ¼ .0214), with an increase of approximately 0.1 month per year, 9 which also was consistent with our study results. Thus, the outcomes of patients with advanced NSCLC from around the world who were enrolled in Phase III trials, along with the outcomes of patients entered on trials that were conducted in North America, seem to have improved consistently over the years.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results were consistent with those from a previous IPD-based analysis of ECOG trials, which reported improved survival in more recent NSCLC trials. 10 Breathnach et al, who investigated the changes in trial characteristics and outcomes of 33 Phase III trials that were initiated from 1973 to 1994 in North America, reported an improvement in survival over time (P ¼ .0214), with an increase of approximately 0.1 month per year, 9 which also was consistent with our study results. Thus, the outcomes of patients with advanced NSCLC from around the world who were enrolled in Phase III trials, along with the outcomes of patients entered on trials that were conducted in North America, seem to have improved consistently over the years.…”
Section: Discussionsupporting
confidence: 91%
“…Breathnach et al also noted that platinum-based therapy was associated independently with survival prolongation (P ¼ .0318). 9 Wakelee et al observed a significant survival advantage from cisplatin in their patients with NSCLC (hazard ratio, 0.882; P < .0001). 10 In addition, we observed a significant survival benefit from cisplatin-based regimens compared with noncisplatin-containing regimens irrespective of the year of trial initiation (an increase of 0.9631 months [28.89 days] with cisplatin; P < .0001) ( Table 3).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The initial therapy for advanced non-small-cell lung cancer (NSCLC) is systemic chemotherapy with a two-drug combination regimen, which often includes a platinum agent, but the median survival of patients treated with such regimens has ranged from only 8 to 10 months. Little improvement in the efficacy of chemotherapy has been made in the last 20 years (Breathnach et al, 2001;Kelly et al, 2001;Schiller et al, 2002).…”
mentioning
confidence: 99%